Protective effect of acquired long QT syndrome in Takotsubo syndrome - Hohneck, Anna; El-Battrawy, Ibrahim; Lang, Siegfried; Ansari, Uzair; Schramm, Katja; Zhou, Xiao-Bo; Borggrefe, Martin; Akın, Ibrahim (Internal medicine journal, 2019)
Background: Clinical variables that predict long-term mortality and recurrence of Takotsubo syndrome (TTS) are not completely understood as the role of acquired corrected QT interval (QTc) prolongation. Aim: To detect the prevalence of QTc interval prolongation in patients with TTS and to evaluate its long-term prognostic impact. Methods QTc intervals were analysed in 105 patients presenting with symptoms of TTS. These patients were included in an ongoing retrospective cohort database. The cohort was subsequently subdivided into two groups based on the presence (long QT (LQT) group, n = 73, 69.52%) or absence (non-long QT (non-LQT) group, n = 32, 30.43%) of QTc interval prolongation. Patients were followed up over a mean period of 4.2 years. The rate of life-threatening arrhythmia during the first 30 days in the LQT group was comparable with the non-LQT group (10.9 vs 12.5%), whereas in-hospital mortality and 30-day mortality occurred less frequently in the LQT group (2.7 vs 18.75%, P < 0.01). Results: During this time span, 17 (23.3%) patients with acquired LQT syndrome died, whereas 14 (43.7%) patients with non-LQT duration died. Kaplan-Meier survival rates were significantly higher in the LQT group than those in the non-LQT group (Log-rank-test, P = 0.02). On multivariate analysis, the QTc interval was an independent negative predictor of all-cause mortality (P = 0.02). Conclusion: The QTc interval at admission is an independent negative predictor of long-term adverse outcome in patients with TTS.
Gesehen am 12.09.2019
First published: 26 November 2018